Airy Fairy- magic mess! how can one little fairy get into such big trouble? - Ryan, Margaret; Murfin, Teresa (London Scholastic children's book, 2004)
It's Fairy Gropplethorpe's rainbow birthday and all the fairies at the Academy for Good Fairies are using magic spells to make her a special surprise. All except Airy Fairy. She isn't good at spelling at the best of times and with Scary Fairy up to her usual tricks there are plenty of opportunities for a muddled fairy to mess up